2013
DOI: 10.1080/10934529.2013.838873
|View full text |Cite
|
Sign up to set email alerts
|

UV light photo-Fenton degradation of polyphenols in oolong tea manufacturing wastewater

Abstract: The UV light photo-Fenton degradation of oolong tea polyphenols in tea manufacturing effluent that color the wastewater to a dark brown has been examined. In order to elucidate the photo-Fenton degradation mechanism of oolong tea polyphenols and find the optimal dosages of the Fenton reagents, systematic study has been conducted. For the UV light photo-Fenton degradation of oolong tea effluent being 70 mg-(polyphenol) L(-1), the optimum dosages of Fenton reagents were found to be 20 mgL(-1) of total Fe and 500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Contrary, the overall reaction rate is declined with overdosing H 2 O 2 rather than the optimal concentration, since the excess peroxide reacts with the OH • radicals and hinder them rather than creating them. Additionally, perhydroxyl radicals, HO 2 , are generated which have less oxidizing efficiency than OH • radicals and this is so‐called scavenging effect (Chu, 2001; Sabaikai et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Contrary, the overall reaction rate is declined with overdosing H 2 O 2 rather than the optimal concentration, since the excess peroxide reacts with the OH • radicals and hinder them rather than creating them. Additionally, perhydroxyl radicals, HO 2 , are generated which have less oxidizing efficiency than OH • radicals and this is so‐called scavenging effect (Chu, 2001; Sabaikai et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed a negligible increase from 77.5% to 78.3% in removal efficiency when H 2 O 2 dosage further increased from 100 to 120 mmol/L. It can be interpreted that the excessive H 2 O 2 acts as a scavenger of ∙OH, but the produced HO 2 ∙ (Equations ( 5 )–( 7 )) has much lower oxidation capacities [ 38 ]. Therefore, the optimum H 2 O 2 dosage was found to be 100 mmol/L for advanced treatment of the pesticide-containing wastewater by the MWEUV/Fenton: …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies, such as the work by Tum et al [28] reported the destruction of black tea by ZnO application. Zhang et al [29] degraded black tea by applying gut microbiota; Maghanga et al [30] decolourized black tea by electrocoagulation, while Sabaikai et al [31] reported the decolourization of oolong tea species by the photo-Fenton process. To the best of the knowledge of the authors, the comparative application of both ZnO and TiO 2 under varying light sources for the abatement of rooibos and black tea have not been previously reported.…”
Section: Introductionmentioning
confidence: 99%